2019
DOI: 10.1177/0093854819826213
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Adverse Childhood Experiences on Internalizing Versus Externalizing Outcomes

Abstract: This study examines the effects of adverse childhood experiences (ACEs) on the risk of internalizing or externalizing outcomes among juveniles. While myriad research has investigated the impacts of ACEs on internalizing and externalizing outcomes, it is unclear whether ACEs have a stronger link to one outcome over the other when controlling for other factors. Using a sample of 30,909 youth who exclusively exhibited internalizing ( n = 1,030) or externalizing problems ( n = 29,879), regression techniques and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
71
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(85 citation statements)
references
References 104 publications
10
71
1
3
Order By: Relevance
“…The abuse impacted on several aspects of their lives, such as their relationships with others, their self-respect, and their ability to cope with everyday life. Research has shown CSA to be predictive of internalizing outcomes ( Muniz et al, 2019 ), and many of the consequences described in the interviews match those that several decades of research on offline CSA have reported, namely general depressive symptoms, re-victimization, sexual problems, anxiety, poor self-esteem, and interpersonal problems ( Paolucci et al, 2001 ; Maniglio, 2009 ).…”
Section: Discussionmentioning
confidence: 67%
“…The abuse impacted on several aspects of their lives, such as their relationships with others, their self-respect, and their ability to cope with everyday life. Research has shown CSA to be predictive of internalizing outcomes ( Muniz et al, 2019 ), and many of the consequences described in the interviews match those that several decades of research on offline CSA have reported, namely general depressive symptoms, re-victimization, sexual problems, anxiety, poor self-esteem, and interpersonal problems ( Paolucci et al, 2001 ; Maniglio, 2009 ).…”
Section: Discussionmentioning
confidence: 67%
“…Although direct evidence linking ACEs to deficits in self-control (as conceptualized by Gottfredson & Hirschi, 1990) is absent from the literature, a small body of research reports that ACEs are associated with variation in concepts tangentially related to self-control. This includes externalizing behaviors (Hunt, Slack, & Berger, 2017; Muniz et al, 2019), impulsivity (Perez et al, 2018), a lack of future orientation (Craig, 2019), negative emotionality (Wolff & Baglivio, 2017), and poor delay of gratification (Evans, Fuller-Rowell, & Doan, 2012). Hunt and colleagues (2017), for example, found that children with two ACEs were 3.4 times more likely to display externalizing behaviors that called for professional attention, relative to children with zero ACEs.…”
Section: Aces and Associated Outcomesmentioning
confidence: 99%
“…Cicchetti and Toth, 2005; Corso et al, 2008; Draper et al, 2008; Fergusson et al, 2008; Gould et al, 2012; Shin et al, 2013). These include mental health problems such as depression, anxiety, substance abuse, eating disorders, suicidal symptomatology, psychosis and personality disorder (Bendall et al, 2008; Muniz et al, 2019; Norman et al, 2012; Teicher and Samson, 2013) and a worse-than-usual response to standard treatment approaches to ameliorate them (Nanni et al, 2012; Teicher and Samson, 2013).…”
Section: Introductionmentioning
confidence: 99%